THE IMPORTANCE OF INTRODUCING THE SUBJECT "EDUCATION" IN GENERAL SECONDARY SCHOOLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, the author highlights the legal basis for the introduction of the subject “education “in general education schools in our country and the importance of teaching the subject” education " in general education schools.